Test information and its applications - Trakas, Gediminas (Information & Media, 1997)
The item and test information functions play key roles in the item response theory. They allow to estimate the standard errors of measurement for each item at a given level of examinee's ability q. Another important aspect of the application of the item information functions is the determination of the contribution of an individual item to the precision of the total test. The article introduces the concepts of the item and test information functions and suggests some methods of the application of them in the test preparation and interpretation of test results. Some analysis of an impact of the item format (multiple-choice and open-ended) on the test results is presented in this article. This study is based on the data collected through the Third Mathematics and Science.
Keywords: -